Crop Rotations and Their Impact on Soil Fertility - Ismailov Uzaqbay Embergenovich (International Journal on Integrated Education, 2022)
In the conditions of saline lands of the Republic of Karakalpakstan, in order to study the effect of crop rotation on soil fertility, field experiments were carried out. Based on the results of the studies, it was found that in order to increase soil fertility, i.e. a positive humus balance towards the end is achieved by using alfalfa in the rotation as a cotton fore crop. With no alfalfa crop rotation, the humus balance by the end of the rotation is negative.